Teacher’s Beliefs and Practices in Integrating Digital Game-Based Learning in a Technology-Integrated School - Miranti Miranti; Dyah Setyowati Ciptaningrum; Lusi Nurhayati (English Department FBS UNP, 2025)
This study explores an English teacher's beliefs and practices in integrating Digital Game-Based Learning (DGBL) within an EFL classroom in a technology-integrated school in Medan, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews with one teacher and teaching materials analysis, providing comprehensive insights into the teacher's perspectives and classroom practices. The data analysis technique employed in this research was thematic analysis. The findings revealed that the teacher believed DGBL was a flexible and engaging pedagogical tool that aligns 21st-century learning principles and fosters student-centered instruction. The teacher frequently utilized tools such as Kahoot, Quizziz, and Wordwall to enhance student engagement and interactivity. Despite its benefits, challenges were identified, including limited suitability of DGBL for all materials, difficulty in assessing comprehension, and occasional technical barriers such as poor internet connectivity. The teacher emphasized the importance of balancing DGBL with traditional teaching methods to address diverse learning preferences and objectives. Additionally, the lack of formal training in DGBL integration highlighted a gap in professional development, suggesting a need for targeted training and administrative support. The study underscores the potential of DGBL to enhance student engagement and teacher innovation while identifying areas for improvement. It recommends future research on game design, feedback mechanisms, and collaboration to optimize learning outcomes alongside structured professional development for educators integrating DGBL into their practices.